1992
DOI: 10.1164/ajrccm/146.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Leukotriene E4from the Urine of Patients with Airway Obstruction

Abstract: The urinary excretion of leukotriene E4 (LTE4) was measured in subjects presenting for emergency treatment of airway obstruction. A total of 72 subjects presenting with airway obstruction performed peak flow determinations before and after three treatments with nebulized albuterol given at 20-min intervals. Of these subjects, 22 more than doubled their peak flow rates, while 19 failed to increase their peak flow rates more than 25% during the treatment period. These groups were designated "responders" and "non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(111 citation statements)
references
References 13 publications
3
105
0
3
Order By: Relevance
“…Besides mast cells, eosinophils are the main source of CysLTs which contribute not only to bronchoconstriction and airway hyperreactivity 39, but as in the case of LTE 4 also to eosinophil recruitment 40. Increased levels of LTE 4 can be detected in urine 41, BALF 42, and exhaled breath condensate 43 of patients after allergen challenge. Accordingly, mass spectrometric analysis of BALF from OVA‐challenged mice revealed slightly increased LTC4 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides mast cells, eosinophils are the main source of CysLTs which contribute not only to bronchoconstriction and airway hyperreactivity 39, but as in the case of LTE 4 also to eosinophil recruitment 40. Increased levels of LTE 4 can be detected in urine 41, BALF 42, and exhaled breath condensate 43 of patients after allergen challenge. Accordingly, mass spectrometric analysis of BALF from OVA‐challenged mice revealed slightly increased LTC4 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A quantitative RT-PCR analysis in the mouse revealed that GPR99 mRNA is highly expressed in kidney, testis, and smooth muscle (23). Given that CysLT 1 R and CysLT 2 R are also expressed on smooth muscle cells in airways and blood vessels (3,4,28,29), expression and function of GPR99 on smooth muscle may be affected by the presence of CysLT 1 R and CysLT 2 R. LTE 4 has a sufficient biologic half-life to be excreted into the urine (30), and urinary LTE 4 excretion is significantly increased in spontaneous acute asthma flares (22). Asthmatic individuals show LTE 4 -induced bronchoconstriction as an aerosol in the same concentration range as LTD 4 and LTC 4 (31,32), and LTE 4 potentiates airway hyperresponsiveness to histamine (33).…”
Section: Gpr99 Mediates Lte 4 -Induced Ear Edema In the Cysltr1/ Cysltr2mentioning
confidence: 99%
“…Unexpectedly, LTE 4 elicited more edema in the Cysltr1/Cysltr2 Ϫ/Ϫ mice than LTD 4 or LTC 4 at the same dose and showed a 64-fold increase in potency in the Cysltr1/Cysltr2 Ϫ/Ϫ mice as compared with WT mice, revealing a ligand preference for an unidentified receptor (19). Such a receptor could be important in asthma both because there is heterogeneity to the benefit of CysLT 1 R antagonists (20,21) and because LTE 4 , unlike transient LTC 4 and LTD 4 , is sustained at levels that even * This work was supported, in whole or in part, by National Institutes of Health provide a urinary biomarker for the 5-lipoxygenase/LTC 4 synthase pathway (22).…”
mentioning
confidence: 99%
“…Cysteinyl leukotrienes (cysLTs), leukotriene C 4 (LTC 4 ), LTD 4 , and LTE 4 are proinflammatory lipid mediators with pathobiologic function in asthma. LTE 4 , the stable cysLT, is a weak agonist for the type 1 and type 2 cysLT receptors (CysLTRs), which constrict airway smooth muscle, but elicits airflow obstruction and pulmonary inflammation in patients with asthma.…”
mentioning
confidence: 99%
“…LTE 4 , the stable cysLT, is a weak agonist for the type 1 and type 2 cysLT receptors (CysLTRs), which constrict airway smooth muscle, but elicits airflow obstruction and pulmonary inflammation in patients with asthma. We recently identified GPR99 as a high-affinity receptor for LTE 4 that mediates cutaneous vascular permeability.…”
mentioning
confidence: 99%